Analysis of Requirements in the Context of Multi-Platform Dropshipping Application Using Activity Theory - Basaruddin, Nur Atiqa; Nik Ahmad, Nik Azlina (Journal of Computing Technologies and Creative Content, 2021)
Nowadays, a change has taken place in organizations that have significantly transformed the conduct of business. This impact on the business model resulted in a huge growth in e-commerce and brings numerous values to the customers, such as the data access of products at the cheapest cost, in a short amount of time and with a variety of choices. The main factor behind the growth of e-commerce is the Internet, where the expansion into this sector has helped many established and start-up companies. This paper proposes a method that uses activity theory to analyze the requirements of multi-platform system applications. It then explores the case study of the dropshipping sales management application and shows the results of the study of its requirements analysis using activity theory.